Ecophotography as Environmental Communication in Post-Mining Bangka Belitung: Visual Narratives of Ecological Issues - Iksander Iksander; Gusmulyana Gusmulyana (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2026)
Digital technology has transformed patterns of environmental communication and positioned photography as a strategic medium for fostering ecological awareness. In the context of tin mining in Bangka Belitung, the role of local photographers deserves scholarly attention because their work demonstrates that photography functions not merely as a visual product but also as a form of environmental advocacy. This study aims to identify the roles of local photographers in constructing ecophotographic narratives for post-mining nature conservation campaigns. It employs a descriptive qualitative method, supported by Strauss and Corbin’s analytical approach and Stuart Hall’s theory of representation, to examine how ecological meanings are constructed, negotiated, and communicated to audiences. The findings reveal four interrelated roles performed by local photographers. First, they act as designers of visual narratives by combining images of ecological wounds with hopes for environmental recovery through local symbols, such as kolong biru, post-mining old towns, birds, and former mining landscapes. Second, they serve as mediators between photographic subjects and wider audiences by using diverse Instagram content to expand the circulation of ecological messages. Third, they embody the values of visual honesty, empathy toward humans and nature, and persuasive criticism by aestheticizing environmental damage so that ecological concerns can be more easily understood by digital audiences. Fourth, they function as local storytellers who present “voices from within” through varied visual approaches, despite resistance from miners. Overall, these roles show that local photographers contribute significantly to shaping environmental awareness and encouraging public reflection on post-mining landscapes in Bangka Belitung.